Interactive e-learning of hajj using graceful interaction concept for elderly / Siti Fazreen Abdul Rashid - Abdul Rashid, Siti Fazreen (2014)
The growth of technology has spurred research towards the creation of human values through digital engagement. Research on human computer interaction (HCI) has begun to explore dimensions of human value derived from the aesthetics of interaction. To further explore new forms and perspective of aesthetics of interaction, graceful interaction design has been conceptualized to enrich human computer engagement. The aim of this research is to apply graceful interaction concepts in development of e-learning hajj course ware for elderly. The design elements of the graceful interaction concept adapted from the theory of Laban Movement Analysis which focus on formal movement quality has been mapped in hajj course ware. The design guideline for elderly is identified to meet the elderly needs. The Visual Information Seeking Mantra (VISM) is identified and applied as a flow of interaction guideline for elderly. Then, a user testing is conducted to get their response about the course ware. The finding of user testing shows that the design elements able to create a graceful interaction and enhance user experience.